2014
DOI: 10.1259/dmfr.20130287
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metallic posts in the detection of vertical root fractures using different imaging examinations

Abstract: Objectives: To assess the influence of metallic posts in the detection of simulated vertical root fractures (VRFs) using the following imaging examinations: 2 cone beam CT (CBCT) systems [CBCT1: NewTom ® 3G (QR Srl, Verona, Italy) and CBCT2: i-CAT Next Generation ® (Imaging Sciences International, Hatfield, PA)] and film and digital radiographs. Additionally, the influence of the orientation of the fracture line in the detection of VRFs was evaluated. Methods: 100, human, single-rooted endodontically treated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
(70 reference statements)
1
36
0
3
Order By: Relevance
“…24,27 Four studies compared CBCT detectors, and three of them showed that the diagnostic accuracy of image intensifier tube charged coupled devices (IIT/CCDs) was lower than that of flat-panel detectors (FPDs). 12,28,30 The remaining study showed no difference in diagnostic accuracy between FPDs and complementary metaleoxideesemiconductors (CMOSs). 26 Five studies compared the different voxel sizes (400 mm, 300 mm, 250 mm, 200 mm, and 125 mm) in the detection of VRFs, and the results showed that the smaller voxel sizes had a higher diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…24,27 Four studies compared CBCT detectors, and three of them showed that the diagnostic accuracy of image intensifier tube charged coupled devices (IIT/CCDs) was lower than that of flat-panel detectors (FPDs). 12,28,30 The remaining study showed no difference in diagnostic accuracy between FPDs and complementary metaleoxideesemiconductors (CMOSs). 26 Five studies compared the different voxel sizes (400 mm, 300 mm, 250 mm, 200 mm, and 125 mm) in the detection of VRFs, and the results showed that the smaller voxel sizes had a higher diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 94%
“…One in vitro study showed a diagnostic accuracy of as high as 100%. 28 However, the highest reported diagnostic accuracy in the human studies was only 93% from a sample size of 14 patients. 8 Therefore, the results of the in vitro studies might not reflect the real clinical efficacy in detecting VRFs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…5,8 The presence of image artefacts resulting from radio-opaque materials, such as metals, gutta-percha and root canal sealers, decrease the accuracy of VRF detection using CBCT. [14][15][16][17] A previous study evaluated the shapes of radiolucent areas on periapical radiographs of teeth with VRF and apical periodontitis. 7 The shapes of the radiolucent areas on periapical radiographs of VRF teeth were found to be more complicated than those of non-VRF teeth in endodontically treated maxillary incisors and pre-molars.…”
Section: Introductionmentioning
confidence: 99%